Pengaruh Konsentrasi Sukrosa Terhadap Karakteristik Minuman Sari Buah Sirsak (Annona muricata Linn) Terfermentasi Dengan Isolat Lactobacillus sp. F213 - Tryadi Pradipta, A.A. Gd.; Ayu Nocianitri, Komang; Mayun Permana, I Dewa Gede (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p12, 2020)
Lactobacillus sp. F213 (LbF213) is a lactic acid bacteria (LAB) that has the potential as a probiotic because it can provide health effects for those who consume it, so it is necessary to make efforts to increase the application of LbF213 in the field of food processing. This study aims to determine the effect of sucrose concentration on the characteristics of fermented soursop juice with LbF213 isolates and get the right concentration of sucrose to produce fermented soursop juice with the best characteristics. The experimental design used was Randomized Block Design with sucrose treatment of 0%, 3%, 6%, 9%, and 12%. Each treatment was repeated 3 times to obtain 15 experimental units. LAB total was analyzed descriptively and the other variables were analyzed by ANOVA and if there was an influence between treatments continued with Duncan test. The results showed that sucrose treatment affected total sugar, taste (hedonic), sour taste and sweet taste (score), overall acceptance (hedonic). The 6% sucrose treatment produced the best fermented soursop juice with a total LAB 1,27 x 1010 cfu/ml, total sugar 12.91%, total acid 1.57%, pH 3.83, color and aroma rather liked, with a slight taste sour and rather sweet liked, and overall acceptance liked. Keywords: fruit juice, lactobacillus sp. F213, sucrose concentration.